Problems and perspectives in the identification of new occupational carcinogens. - Vineis, P.; Blair, Aaron (Scandinavian Journal of Work, Environment & Health, 1992)
Occupational studies have played a major role in the identification of chemical carcinogens. There still remain, however, substances and occupations that deserve further evaluation. The more careful control of potentially hazardous exposures in most developed countries has necessitated a change in the conduct of epidemiologic investigations. The lowering of exposures and the lack of a simple correspondence between specific exposures and one or a few jobs underscores the need for careful reconstruction of historical exposures. The most successful reconstructions will include the integration of monitoring data, historical information on work histories and work practices, and use of biochemical markers.